PEMBERDAYAAN MASYARAKAT KAMPUNG TIDAR MENUJU KAMPUNG ASRI DAN LESTARI DIMASA PANDEMI COVID-19: PEMBERDAYAAN MASYARAKAT KAMPUNG TIDAR - Windarto, Windarto; Martini, Martini; Samsinar, Samsinar (KRESNA: Jurnal Riset dan Pengabdian Masyarakat, 2021)
Community service activities are a form of implementation of one of the Tri Dharma of Higher Education. This program will be implemented in August 2021 which is located in East Sudimara Village, Ciledug District, Tangerang. The theme that will be implemented is the theme of Environmental Conservation in Kampung Tidar. With the targets and programs that have been designed, it is hoped that it will be able to build the interest of the local community to continue to be aware of the environment and be able to develop and maximize their potential